2021
DOI: 10.3390/ijerph18031283
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fixed Dental Crowns and Volatile Sulphur Compounds

Abstract: Objectives: The aim of this study was to investigate and compare the level of halitosis in patients with/without fixed crowns and in addition the influence of various crown parameters on halitosis was also explored. Methods: In total, 96 subjects (fixed crowns = 52; no crowns = 44) participated in the study. The levels volatile sulphur compounds (VSCs) of hydrogen sulphide (H2S), methyl mercaptan (CH3SH), and dimethyl sulphide (CH3SCH3) were evaluated with breath samples using gas chromatography and used for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Fixed dentures, despite the fact that they are a significantly different in construction comparing to removable dentures may also make it difficult to maintain proper oral hygiene—not only through the retention of food debris and the deposition of dental plaque [ 15 ], but also due to the inaccessibility to daily hygiene procedures and impaired ability of their self-cleaning by saliva [ 18 ]. The values obtained from a study with the Oral Chroma device showed the presence of halitosis in 65.9% of patients with dental crowns, and only in 32.69% without fixed dentures in the oral cavity [ 19 ]. The influence of the position of the crown edge, the marginal integrity, and the contour of the crown on the presence of halitosis was investigated.…”
Section: Halitosis In Dental Prostheticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fixed dentures, despite the fact that they are a significantly different in construction comparing to removable dentures may also make it difficult to maintain proper oral hygiene—not only through the retention of food debris and the deposition of dental plaque [ 15 ], but also due to the inaccessibility to daily hygiene procedures and impaired ability of their self-cleaning by saliva [ 18 ]. The values obtained from a study with the Oral Chroma device showed the presence of halitosis in 65.9% of patients with dental crowns, and only in 32.69% without fixed dentures in the oral cavity [ 19 ]. The influence of the position of the crown edge, the marginal integrity, and the contour of the crown on the presence of halitosis was investigated.…”
Section: Halitosis In Dental Prostheticsmentioning
confidence: 99%
“…The influence of the position of the crown edge, the marginal integrity, and the contour of the crown on the presence of halitosis was investigated. The parameters found to be defective included the subgingival margin, over-contouring, and crowns with leaking margin; the levels of volatile sulfur compounds were significantly higher in these patients compared to patients with non-defective crown parameters [ 19 ]. Thus, improperly made crowns significantly worsen the hygienic conditions and the microbiota of the oral cavity, resulting in a high frequency of halitosis [ 19 ].…”
Section: Halitosis In Dental Prostheticsmentioning
confidence: 99%
See 1 more Smart Citation